2017
DOI: 10.1002/psp4.12260
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Performance of Physiologically Based Pharmacokinetic Models for the Effect of Food on Oral Drug Absorption: Current Status

Abstract: A comprehensive search in literature and published US Food and Drug Administration reviews was conducted to assess whether physiologically based pharmacokinetic (PBPK) modeling could be prospectively used to predict clinical food effect on oral drug absorption. Among the 48 resulted food effect predictions, ∼50% were predicted within 1.25‐fold of observed, and 75% within 2‐fold. Dissolution rate and precipitation time were commonly optimized parameters when PBPK modeling was not able to capture the food effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 33 publications
2
72
0
Order By: Relevance
“…In a recent study, the FDA colleagues reviewed previously published food effect PBPK models. 11 The authors found that for 48 food effect AUC ratio predictions,~50% were within 1.25-fold. This accuracy is less than that which has been reported for PBPK predictions of enzyme induction (77%), or inhibition (81%) where modeling has been used to waive clinical studies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a recent study, the FDA colleagues reviewed previously published food effect PBPK models. 11 The authors found that for 48 food effect AUC ratio predictions,~50% were within 1.25-fold. This accuracy is less than that which has been reported for PBPK predictions of enzyme induction (77%), or inhibition (81%) where modeling has been used to waive clinical studies.…”
Section: Discussionmentioning
confidence: 96%
“…The U.S. Food and Drug Administration (FDA) scientists recently summarized some of the limitations in a literature review across BCS I-IV classes, which highlighted the need for an agreed and optimized workflow for prediction of food effect. 11 In this study, we present a workflow for food effect predictions for immediate-release (IR) formulations of BCS I and BCS II compounds ( Fig. 1) for which clinical data are available in one prandial state, fasted or fed.…”
Section: Introductionmentioning
confidence: 99%
“…The use of in silico PBBM modelling to develop CRDS is becoming more widespread, and several examples of this have been presented by both Industry and Regulators [6,[14][15][16]. This approach offers enhanced mechanistic insight into the factors that influence absorption and the interplay between in vitro and in vivo performance.…”
Section: Clinically Relevant Specifications: Connecting Product Perfomentioning
confidence: 99%
“…In this study, PBPK modelling described 50% of the observed food effect within a predefined boundary of 25%. The successful application of PBPK modelling in food‐effect predictions requires model verification against in vivo clinical data (Li, Zhao, Pan, & Wagner, ).…”
Section: Introductionmentioning
confidence: 99%